Military communications from ancient times to the 21st century - Sterling, Christopher H. (ABC-CLIO, 2008)
An encyclopedia of all types of communications ever used by any military service around the world, from fire signals to VoIP (Voice over Internet Protocol), Military Communications: From Ancient Times to the 21st Century opens with a superb overview essay, which provides a succinct history of communications and an excellent introduction to a fascinating topic. The essay is followed by 322 separate entries covering innovations, people, locations, organizations, and conflicts. Most entries are around one page in length, and each includes a list of sources. Plenty of black-and-white illustrations accompany the text. Access is facilitated by numerous cross-references in addition to a complete listing of the entries at the beginning of the encyclopedia and a single index at the end. Editor Sterling has published many works on communications and is a professor of media and public affairs. The contributing authors come from around the world and include authors from academe, the private sector, the armed services, and nongovernmental organizations. Most of the authors are from North America, which is reflected in the Western focus of the work. However, there are plenty of non-Western authors and entries. The four appendixes-"Military Communications Museums," "Military Communications Conferences," "Glossary of Acronyms," and "Further Reading: A Basic Bibliography"-are useful additions. As much a history of all forms of communications as a military history, this volume will be an essential reference work for libraries collecting in those areas. Recommended for academic and large public libraries.